1998
DOI: 10.1111/j.1699-0463.1998.tb01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus antigen in macrophage/microglial cells and astrocytes of subacute sclerosing panencephalitis

Abstract: de Siqueira, M. M. Measles virus antigen in macrophage/microglial cells and astrocytes of subacute sclerosing panencephalitis. APMISIn two patients with subacute sclerosing panencephalitis (SSPE) of 10 and 25 months duration we demonstrated by immunohistochemistry the presence of measles-virus nucleocapsid antigen (MVNA) in CD68+ cells and astrocytes of brain tissues. In both cases, CD68+ hematogenous monocyte/ macrophages and perivascular microglial cells (MO) were found infiltrating the brain parenchyma, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…MV infection of the central nervous system (CNS) is a rare event (27,30). Oligodendrocytes and neurons are the predominantly infected cell types, although infected astrocytes have also been described (1,30,31,34). In this study we have used two astrocytoma cell lines, the first being GCCM cells, which have been used to study MV cell-to-cell spread (13a).…”
Section: Measles Virus (Mv) Is a Morbillivirus Which Belongs To Thementioning
confidence: 99%
“…MV infection of the central nervous system (CNS) is a rare event (27,30). Oligodendrocytes and neurons are the predominantly infected cell types, although infected astrocytes have also been described (1,30,31,34). In this study we have used two astrocytoma cell lines, the first being GCCM cells, which have been used to study MV cell-to-cell spread (13a).…”
Section: Measles Virus (Mv) Is a Morbillivirus Which Belongs To Thementioning
confidence: 99%
“…Moreover, dendritic cells (DC) can be infected in vitro (11,14,34). In cases where the virus disseminates in the central nervous system (13), CD68-positive hematogenous macrophages/microglia cells are infected (25).…”
mentioning
confidence: 99%
“…The invariably fatal disease occurs several years after primary MV infection [2] and is characterized by uncontrolled replication of mutated and defective MV in neuronal and glial cells [3]. MV infection that occurs before 2 years of age is associated with a risk for SSPE that is 16 times as high as the risk associated with infection after 5 years of age [4].…”
Section: Rapid Progressive Subacute Sclerosing Panencephalitis In a 2mentioning
confidence: 99%
“…Although congenital hypothyreosis has been associated with a variable degree of impaired immune function, there were no clinical signs of immunodeficiency in our patient. Molecular-biological investigations have revealed that the persistence of MV in the CNS is associated with and most likely caused by a defective viral replication, which allows MV to survive intracellularly during incubation period while remaining inaccessible to host immune surveillance [3,12]. The susceptibility of the host, as well as the host's age and immune status, at the time of infection also constitute significant factors for disease progression [12].…”
Section: Rapid Progressive Subacute Sclerosing Panencephalitis In a 2mentioning
confidence: 99%
See 1 more Smart Citation